Pro Arte Quartet: Three concerts devoted to string quartets by Ludwig van Beethoven (New York, 2020)
Program for a three-concert series of Beethoven String Quartets by the Pro Arte Quartet at Cornell University, on February 24 and 27 and March 3, 1941. The quartet members included Antonio Brosa, Laurent Halleux, Germain Provost, and G. warwick Evans.